ANALISIS STRUKTUR BATIN PUISI “DENGAN PUISI, AKU” KARYA TAUFIK ISMAIL - Susi Astriani; Yusep Ahmadi; Wika Nengsih (IKIP Siliwangi, 2022)
Poetry is the most unique literary work because it is created from the poet's deepest contemplation, poetry is not just a work of art but an outpouring of a writer when he is happy, or when he is sad. Poetry is a very elegant way to convey the heart and express all the events that occur in everyday life to every human being. This poem has two structures, namely the physical structure and the inner structure. The author chose